3D finite element study on interacting crack problems in offshore pipelines - Goh, Darius Jia Kang (Nanyang Technological University, 2024)
Over time, the world has heavily relied on offshore oil and gas for energy needs, with offshore pipelines serving as a traditional means of transporting these resources. Corrosion-resistant Alloy (CRA) is commonly used for such pipelines, which can span hundreds of kilometres from offshore platforms to onshore refineries. One example of a CRA, a super duplex stainless steel is SAF 2507, which is a widely used alloy in offshore and marine applications. These pipelines are typically assembled by welding shorter sections of pipe together, but during this process, defects like cracks and porosity may arise due to environmental factors and bending stress. These flaws are critical as they can impact the pipe's lifespan, potentially leading to fractures over time. The growth of cracks can be accelerated by various forces and pressures, including linear force, bending moment, and hydrostatic pressure.